2022
DOI: 10.1021/acs.iecr.2c02599
|View full text |Cite
|
Sign up to set email alerts
|

Internal Optimization for Enhancing the Microbubble Dispersion Characteristics of a Stirred Tank

Abstract: Little research on the microbubble-aided transport characteristics in stirred vessels is reported. This motivates the present efforts to experimentally analyze the effects of operating condition, impeller, baffle, and sparger on the gas dispersion characteristics in a stirred tank with microbubble aeration. It is found that the number of large bubbles gradually increases with the increase of impeller speed, which is completely opposite of the results in the conventional gas−liquid stirred tank. Without baffles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In Dth 27.0, the test tank is a stainless-steel stirred tank with a 2 m 3 volume made for bioleaching. In a recent work, it was found that the microbubble-fluid distributor has a significant impact on the gas–liquid mass transfer performance . Considering that the large volume of a 2 m 3 reactor is more likely to cause nonuniform bubble distribution, a spider-gas sparger distributor is used to disperse the microbubble–fluid mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Dth 27.0, the test tank is a stainless-steel stirred tank with a 2 m 3 volume made for bioleaching. In a recent work, it was found that the microbubble-fluid distributor has a significant impact on the gas–liquid mass transfer performance . Considering that the large volume of a 2 m 3 reactor is more likely to cause nonuniform bubble distribution, a spider-gas sparger distributor is used to disperse the microbubble–fluid mixture.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work, it was found that the microbubble-fluid distributor has a significant impact on the gas−liquid mass transfer performance. 37 Considering that the large volume of a 2 m 3 reactor is more likely to cause nonuniform bubble distribution, a spider-gas sparger distributor 38 is used to disperse the microbubble−fluid mixture. It has six arms made of 0.20 m diameter stainless-steel tubes soldered to the center cylinder of the gas sparger and dozens of holes with diameters d 0 = 2−4 mm located on the side of each arm facing downward.…”
Section: Dth 42 Of Venturi Microbubblementioning
confidence: 99%
“…Thermodynamics, Transport, and Fluid Mechanics is the topic area in I&ECR with the highest rate of participation of industrial authors as a percentage of the articles published. The collection includes a study on thermodynamic performance of three different autothermal chemical gas looping operation modes, the extrusion of polyacrylonitrile fibers using a very high L/D extruder (recognized with a cover in May 2023), description of mass transfer in gas–liquid flow, a kinetic model for CO 2 adsorption on amine-functionalized MOFs, description of microbubble transport in stirred reactors, two articles using computational fluid dynamics, , and a view on the future of thermodynamics following the results of an industrial survey …”
mentioning
confidence: 99%